High performance non-symmetric multi-h CPFSK modulator and demodulator design - Cuthbert, James (Department of Electrical Engineering, 2016)
The continuity properties of the CPFSK signal at it's symbol-period boundaries reveals an inherent memory contained in the transmitted signal. This is utilized as an error correction property. Furthermore, it was shown that the Multi-h CPFSK construction can be accomplished through the combination of a block constructing the memoryless component of the signal and either a block of digital logic circuitry or a continuous phase encoder constructing the memory component. The implementation of the first method was seen to function through simulations performed by using the TESLA simulation package. An extensive search for good Multi-h CPFSK h-sets was performed. The criteria for determining the performance of these h-sets was the Probability of Error gains over Minimum Shift Keying. The method of search was novel to this work. Specifically, a genetic search algorithm known as the Population Based Incremental Learning algorithm was utilized. The algorithm was implemented through the C++ programming language Faster error correction convolutional decoding algorithms were reviewed. Certain decoders exhibit lighter hardware demands, and in specific applications, are less susceptible to erasure problems. The Fano algorithm was selected as the best alternative to the Viterbi algorithm and was modified for the CPFSK implementation. The functionality of the implementation was tested using a C++ simulation. Various structures used to implement the synchronization and demodulation of Multi-hCPFSK were investigated. The most comprehensive structure that could be found was a scheme developed by Premji and Taylor using maximum likelihood techniques. This scheme was selected as it can be easily modified for the use with the large state, high speed implementation of non-symmetric Multi-h CPFSK investigated in this thesis. The PBIL algorithm was found to be an efficient method for finding good h-sets with large numbers of phase states. Theoretical gains over MSK using this method were found to be significant. It was concluded that the Fano decoder is highly applicable to the demodulator structure proposed in this thesis and is a preferred alternative to the Viterbi decoder under specific circumstances.